Microwave-assisted hydrothermal synthesis of structurally and morphologically controlled sodium niobates by using niobic acid as a precursor - Paula, Amauri J. [UNESP]; Zaghete, Maria A. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Wiley-v C H Verlag Gmbh, 2008)
There are many advantages to using a microwave as a source of heat in hydrothermal reactions. Because it is a quick and homogeneous way to crystallize ceramic powders, it was used in this work for the production of antiferroelectric sodium mobate (NaNbO3) in a cubic-like form and its intermediary phase, disodium diniobate hydrate (Na2Nb2O6 center dot H2O), with a fiber morphology. The syntheses were carried out by treating niobic acid (Nb2O5 center dot nH(2)O) with NaOH. By changing the reaction time and the concentration of the reactants, particles with different structures and different morphologies could be obtained. The structural evolution of the products of this reaction was elucidated on the basis of the arrangement of the NbO6 octahedral units. Conclusive results were obtained with morphological and structural characterizations through XRD, TEM, MEV, and NMR and Raman spectroscopy. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008).
Keywords: hydrothermal synthesis; crystal growth; niobates; crystal morphology